Uwarunkowania i persektywy dyskusji na temat narodu śląskiego - Trosiak, Cezary (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2009)
Na fali przemian zapoczątkowanych „okrągłym stołem” doszło do pojawienia się w dyskusji socjologów, politologów, etnologów i co ważniejsze polityków, kwestii narodu śląskiego. Problem ten dla badaczy problematyki śląskiej nie był zaskoczeniem, gdyż mniej więcej od początku lat 80. dało się wyraźnie zauważyć dystansowanie się ludności rodzimej Śląska (zarówno Górnego jak i Opolskiego) od jednoznacznego deklarowania swojej przynależności do narodu polskiego czy niemieckiego. Wyjściem pośrednim, szczególnie mocno podnoszonym przez Ślązaków mieszkających w Polsce, było wskazywanie swojej śląskości, jako alternatywy w stosunku do określania tej ludności jako polskiej ludności rodzimej.

The wave of transformations commenced by the ‘round table’ led the issue of the Silesian nation to be discussed by sociologists, political scientists, ethnologists, and – what is more significant – politicians. This issue was far from surprising for the researchers into the problems of Silesia as the native population of (both Upper and Lower) Silesia have clearly distanced themselves from a unanimous declaration of nationality, whether Polish or German, since the early 1980s. It was a semi-solution, adopted particularly by the Silesian living in Poland, to point to their Silesian nationality, as an alternative to being defined as a native Polish population.
The Conditions and Prospects of Discussion Regarding the Silesian Nation
Keywords: Naród śląski